Assessment of TP53, PTEN and AKT gene mutations in tongue squamous cell carcinoma and oral leukoplakia of smokers and non-smokers - Pereira , Glauce Guimarães; Pontes , Flávia Sirotheau Côrrea; Gomes , Carolina Cavalieri; Fonseca, Felipe Paiva; Pontes, Ana Luisa Sirotheau Corrêa; Uchoa, Sue Ann Lavareda Corrêa; Cruz, Samara Silveira da; Burbano, Rommel Mario Rodriguez; Pontes, Hélder Antônio Rebelo (Journal of Oral Diagnosis, 2025)
Oral Squamous Cell Carcinoma (OSCC) is the most common malignant tumor of the oral cavity. It can be preceded by Oral leukoplakia (OL), the most prevalent potentially malignant disorder, which presents a malignant transformation rate which varies from 1,1 to 40,8%, found most commonly in tongue lesions. Smoking is a well-established risk factor for both OL and OSCC. In this study we aimed to investigate loss of heterozygosity (LOH) as well as the frequency and patterns of the mutations in the PTEN, AKT and TP53 genes in OL and tongue squamous cell carcinoma (TSCC) samples of smokers and non-smokers patients. Tissue specimens were obtained from 73 patients: 35 cases of TSCC and 38 cases of high grade OL occurring in the lateral border of the tongue, and PTEN, AKT e TP53 gene mutations were investigated through Fluorescence In Situ Hybridization and genotyping. Differences between the genetic changes studied in the TP53, PTEN and AKT genes in smoking and non-smoking patients were detected. Changes in the TP53 gene did not occur significantly in the OL stage in either smoking or non-smoking patients, whereas changes in the PTEN gene were observed in both OL and OSCC, with a statistically significant difference between smokers and non-smokers. Furthermore, changes in the AKT gene did not occur with high frequency in either OL or carcinomas, regardless of smoking status, suggesting that disruptions in the critical PI3K pathway are primarily due to genetic changes in PTEN rather than in the AKT gene.